Features of surgical tactics in traumatic amputations of limbs - E. V. Ponomarenko (Zaporozhye State Medical University, 2016)
The frequency of traumatic amputations is constantly growing, which is associated with the development of transport and modern technology, military conflicts. Aim: To improve the results of treatment of patients with wound and functional defects after injury by developing a comprehensive program of surgical treatment to restore the shape and function of the trunk and limbs. Materials and methods. From 2010 to 2016 52 patients were observed in the clinic. Traumatic amputations at the hip level were observed in 14 patients, at the level of the upper third of the tibia - in 7 patients, at the level of the lower third of the tibia - 3, foot - 6. Simultaneous amputation of two lower limbs was observed in 2 patients. Amputation of upper limbs at shoulder level was observed in 3 patients, hand - 2, fingers - 15 patients. Among the reasons of limb amputations road traffic injuries occupied the leading position - 77.8 %. Combined injury (mechanical and thermal) was observed in 1 case - there was a burn of amputated limb. In 31 cases (59.6 %) there was complete amputation of a limb, incomplete - in 21 cases (40.4 %). Results. As a result of these tactics, only in 3 cases we had to do limb reamputation due to the inconsistency of the stump. In 22 patients for the conservation of sufficient length and the optimum shape of the stump the imposition of primary sutures was not made. At the stage of recovery of tissue covering the stump in 16 cases the closure of wound defects with simple split skin graft was fulfilled, 3 - with plastic by local tissues, 4 - islet flap on the peripheral stalk, 1 - plastic flat bridging flap, 20 operations were performed with tubular migratory classic flap. There were no complications in the postoperative period. Conclusions. The main principles in establishing the indications for reconstruction of large limb segments should be both critical attitude to the operation and strict individual approach to each patient based on the comprehensive evaluation of all the criteria.